Study Second Harmonic Generation of KTP Crystal - Raad S. Alnaily (Journal of Global Pharma Technology, 2018)
In this paper, we tried to investigate to display the performance of the pure single potassium Titanyl Phosphate (KTiOPO3 or KTP) crystal of dimension (6×6×3) mm3 as a distinguished proposal model of second harmonic generation and using CW Nd: YAG laser that has the spectral wavelength 1064nm to generate 532nm. The efficiency of the frequency doubler for Nd: YAG laser by means of this proposed crystal element were satisfied with both arrangements. They was13% one step the nonlinear optical properties as third order, such as the nonlinear refractive index and nonlinear absorption were also measured in this work to indicate on the high nonlinearity optics of this electro-optical material with the infrared and visible wavelengths range.Keywords: - Second harmonic generation, second-order susceptibility χ (2), potassium Titanyl phosphate (KTiOPO3 or KTP), Nonlinear refraction index , Nonlinear absorption coefficient, Third order nonlinear optical susceptibility χ(3).